Renal function, congestive heart failure, and amino-terminal pro-brain natriuretic peptide measurement : Results from the probnp investigation of dyspnea in the emergency department (PRIDE) study - ANWARUDDIN, Saif; LLOYD-JONES, Donald M; BAGGISH, Aaron; CHEN, Annabel; KRAUSER, Daniel; TUNG, Roderick; CHAE, Claudia; JANUZZI, James L (Journal of the American College of Cardiology, 2006)
The relationship between renal insufficiency and amino-terminal pro-brain natriuretic peptide (NT-proBNP) levels remains unclear. We examined this relationship in the context of patients who presented to the emergency department of an urban tertiary care medical center with dyspnea. Even in the presence of renal insufficiency, NT-proBNP remained a valuable tool for the diagnosis of acute congestive heart failure and it provides important prognostic information. We sought to examine the interaction between renal function and amino-terminal pro-brain natriuretic peptide (NT-proBNP) levels. The effects of renal insufficiency on NT-proBNP among patients with and without acute congestive heart failure (CHF) are controversial. We examined the effects of kidney disease on NT-proBNP-based CHF diagnosis and prognosis. A total of 599 dyspneic patients with glomerular filtration rates (GFRs) as low as 14.8 ml/min were analyzed. We used multivariate logistic regression to examine covariates associated with NT-proBNP results and linear regression analysis to analyze associations between NT-proBNP and GFR. Receiver-operating characteristic analysis determined the sensitivity and specificity of NT-proBNP for CHF diagnosis. We also assessed 60-day mortality rates as a function of NT-proBNP concentration. Glomerular filtration rates ranged from 15 ml/min/1.73 m2 to 252 ml/min/1.73 m2. Renal insufficiency was associated with risk factors for CHF, and patients with renal insufficiency were more likely to have CHF (all p < 0.003). Worse renal function was accompanied by cardiac structural and functional abnormalities on echocardiography. We found that NT-proBNP and GFR were inversely and independently related (p < 0.001) and that NT-proBNP values of > 450 pg/ml for patients ages <50 years and >900 pg/ml for patients > or =50 years had a sensitivity of 85% and a specificity of 88% for diagnosing acute CHF among subjects with GFR > or =60 ml/min/1.73 m2. Using a cut point of 1,200 pg/ml for subjects with GFR <60 ml/min/1.73 m2, we found sensitivity and specificity to be 89% and 72%, respectively. We found that NT-proBNP was the strongest overall independent risk factor for 60-day mortality (hazard ratio 1.57; 95% confidence interval 1.2 to 2.0; p = 0.0004) and remained so even in those with GFR <60 ml/min/1.73 m2 (hazard ratio 1.61; 95% confidence interval 1.14 to 2.26; p = 0.006). The use of NT-proBNP testing is valuable for the evaluation of the dyspneic patient with suspected CHF, irrespective of renal function.